2020
DOI: 10.1002/chem.202002362
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Based Hybrid Polyion Complexes for Fenton‐Like Reactions

Abstract: An innovative strategy allowing the development of a new generation of easy‐to‐prepare and easy‐to‐use nano‐sized catalysts with high tenability is presented. This strategy is based on the formation of hybrid polyion complexes (HPICs) from the complexation of copper with a block copolymer consisting of an ionizable complexing block and a neutral stabilizer block. These complexes have a well‐defined structure and size with a hydrodynamic diameter around 29 nm. They are stable in aqueous solution over a pH range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
(34 reference statements)
3
27
0
Order By: Relevance
“…Copper is a well-studied Fenton-like reagent with good reaction performance and a wide pH response range [17][18][19] and could also catalyze the conversion of organic peroxide to singlet oxygen through the Russell reaction. 20,21 So far, copper oxide, 22 copper sulfide, 23 copper complex, 24 and copper metal-organic frameworks (MOF) 25 have been extensively studied as CDT reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Copper is a well-studied Fenton-like reagent with good reaction performance and a wide pH response range [17][18][19] and could also catalyze the conversion of organic peroxide to singlet oxygen through the Russell reaction. 20,21 So far, copper oxide, 22 copper sulfide, 23 copper complex, 24 and copper metal-organic frameworks (MOF) 25 have been extensively studied as CDT reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Using HPICs obtained from the complexation of poly­(ethylene oxide)- block -poly­(acrylic acid), PEO- b -PAA, block copolymer, and Au III as a template, Seo et al reported the formation of gold nanoparticles, which can efficiently catalyze the reduction of a series of nitroarenes. Additionally, HPICs formed by the complexation of PEO- b -PAA and Cu 2+ ions exhibited good catalytic activity in the degradation of organic compounds based on a Fenton-like mechanism . Such pioneering studies have paved the way to nanostructures that are easy to synthesize and stable and have high potential as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Chemodynamic therapy (CDT) based on the Fenton reaction, which catalyses hydrogen dioxide (H 2 O 2 ) into highly toxic hydroxyl radicals (•OH) by iron ions, has emerged as a novel therapeutic approach for cancer through oxidative damage of lipids, proteins and DNA [8]. Recently, copper-based Fenton-like reactions with higher reaction rates in a broader pH range showed more possibilities for highly e cient CDT [9][10][11][12][13]. However, copper is a trace element in the body incapable of inducing su cient therapeutic e cacy alone, which would induce toxicity to normal cells at high concentrations [14].…”
Section: Introductionmentioning
confidence: 99%